Assessing Community Participation In Public Policy-Making In Indonesia - Indriati Amirullah; Steviani Batti (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to analyze the extent to which community participation influences the public policy process in Indonesia. The public policy process is a series of actions and decisions that lead to developing and adopting specific public policies. Community participation is critical in this process as it helps shape, define, and implement policies that directly affect them. This study uses qualitative research methodology with data collected through in-depth interviews, document review, and participant observation of stakeholders directly involved in public policy development. The results of this study show that although community participation has a vital role in the policy formulation process, there are still several barriers, such as Lack of information, limited community technical capacity, and other structural issues that affect the level and quality of participation. This study highlights the need to increase transparency and openness of information, educate and build community capacity, and increase community participation in policy formulation. This study contributes to the literature on the role and impact of community participation in the public policy formulation process, especially in the Indonesian context.